Surface Energy Mimicking: Simultaneous Replication of Hydrophilic and Superhydrophobic Micropatterns through Area‐Selective Monomers Self‐Assembly (Adv. Mater. Interfaces 17/2016). Issue 17 (September 2016) - Pardon, Gaspard; Haraldsson, Tommy; van der Wijngaart, Wouter
Abstract : In article 1600404, surface energy mimicking is introduced, enabling spontaneous replication of micropatterns (2D and 2.5D) of different surface energies, and facilitated by self‐assembly of functional mimicking monomers within a polymer matrix by Gaspard Pardon, Tommy Haraldsson, and Wouter van der Wijngaart. Replication of surface energies ranging from hydrophilic to superhydrophobic is demonstrated, as well as self‐assembly of picoliter‐droplet arrays on replicated micropatterns consisting of hydrophilic patches in a hydrophobic surface.